Transforming Self-Help Groups into Small and Medium Enterprises (SMEs) – Odisha leads the way - Sahoo, B; De, H. K.; Saha, G. S. (Indian Farming, 2024)
The article highlights the transformation of Self-Help Groups (SHGs) into Small and Medium Enterprises (SMEs) in India, with a focus on Odisha’s efforts. The article presents data on women’s participation in SMEs across states and emphasizes the benefits of this transformation, sharing success stories from various sectors. Government initiatives and programs are discussed, with a spotlight on Odisha’s Mission Shakti. Authors advocate for imparting entrepreneurial skill among the women enabling them to run enterprises, federate at district level and strengthen the SHG ecosystem.